Composition and Dose of Ameliorant Against C/N Ratio, Soil pH, Plant Phosphate Content on Potato Plants - Parlinah, Linlin; Hamdani, Jajang Sauman; Nurbaity, Anne; Nuraini, Anne (JOURNAL OF TROPICAL SOILS, 2021)
This research aimed to study the addition of ameliorant material in the soil to increase fertility rates, especially for potato plants grown at the height of 750 m above sea level. The experiments were conducted on medium plains 750 m above sea level in the Jatinangor area, Indonesia, with land type Incepticol. The composition of ameliorant consists of Cattle manure, biochar from coconut shells, and dolomite. The seeds of the potatoes used are relatively good varietal when cultivated in a medium plain. The design of the environment used is the group’s random draft repeated three times, the treatment design consists of K0: control; K1: Cattle manure 10 Mg ha-1; K2: Cattle manure 20 Mg ha-1; K3: Cattle manure 8 Mg ha-1, dolomite 1 Mg ha-1, 1 Mg ha-1 biochar; K4: Cattle manure 16 Mg ha-1, dolomite 2 Mg ha-1, 2-Mg biochar ha-1, K5: Cattle manure 8 Mg ha-1, dolomite 2 Mg ha-1; K6: Cattle manure 16 Mg ha-1, dolomite 4 Mg ha-1; K7: Cattle manure 8 Mg ha-1, biochar 2 Mg ha-1; K8: Cattle manure 16 Mg ha-1, biochar 4 Mg ha-1. Results showed that the composition and dose of ameliorant could increase the value of soil pH but have not improved the C/N ratio and absorption of phosphorus plants. The best result was obtained from the composition treatment of 16 Mg ha-1 Cattle manure, 2 Mg ha-1 dolomite, and 2 Mg ha-1 biochar. Soil pH is capable of increased by 16.83%, and the size of the potato bulbs of Class L (450-550 mm) amounted to 35, 11%, size M (350-450 mm) by 25.89%, and size S (200-350 mm) amounting to 34.37% when compared with controls.